Healthy Aging and Muscle Dysfunction: Will Melatonin Help? - Ray Marks (Journal of Aging Research And Healthcare, 2021)
Background Aging is said to represent a declining state that is possibly especially compromised by sleep issues, and declining melatonin levels. Aim This review examined the idea that aging can be favorably influenced in numerous ways by the addition or maintenance of adequate melatonin levels. Specifically, the impact of melatonin on skeletal muscle was the key topic of interest. Method Reviewed were peer reviewed research and review articles specifically pertaining to healthy aging, melatonin, and muscle associated observations. Results Declining melatonin levels greatly impact multiple essential body systems and tissues. Supplements or interventions that heighten melatonin presence appear to have beneficial impacts on aging in general, and muscle function and structure, in particular. Conclusion The use of melatonin early on in the aging process is likely to produce more favorable long-term outcomes than not in cases of deficiency, and should be further investigated.
Keywords: Elderly